Innovative strategy for effective critical laboratory result management: end-to-end process using automation and manual call centre. Issue 8 (3rd May 2012) - Ti, Lian Kah; Ang, Sophia Bee Leng; Saw, Sharon; Sethi, Sunil Kumar; Yip, James W L
Abstract : Background: Timely reporting and acknowledgement are crucial steps in critical laboratory results (CLR) management. The authors previously showed that an automated pathway incorporating short messaging system (SMS) texts, auto-escalation, and manual telephone back-up improved the rate and speed of physician acknowledgement compared with manual telephone calling alone. This study investigated if it also improved the rate and speed of physician intervention to CLR and whether utilising the manual back-up affected intervention rates. Methods: Data from seven audits between November 2007 and January 2011 were analysed. These audits were carried out to assess the robustness of CLR reporting process in the authors' institution. Comparisons were made in the rate and speed of acknowledgement and intervention between the audits performed before and after automation. Using the automation audits, the authors compared intervention data between communication with SMS only and when manual intervention was required. Results: 1680 CLR were reported during the audit periods. Automation improved the rate (100% vs 84.2%; p<0.001) and speed (median 12 min vs 23 min; p<0.001) of CLR acknowledgement. It also improved the rate (93.7% vs 84.0%, p<0.001) and speed (median 21 min vs 109 min; p<0.001) of CLR intervention. From the automation audits, the use of SMS only did not improve physician intervention rates. Discussion: The automated communication pathway improved physician intervention rate and time in tandem with improved acknowledgement rate and time when compared with manual telephone calling. The use of manual intervention to augment automation did not adversely affect physician intervention rate, implying that an end-to-end pathway was more important than automation alone.